KETERLIBATAN ORANG TUA DALAM PENDAMPINGAN PERSIAPAN BAPTIS BAYI SEBAGAI PEMENUHAN JANJI PERKAWINAN - Hia, Maria Epydermian; Sulistiyo, Robertus Joko (PERDIKKATI (Perkumpulan Pendidikan Keagamaan Katolik Indonesia), 2022)
The purpose of this study is to determine the involvement of parents following the assistance of infant baptism preparation as a means to fulfill their marriage vows. This research uses a qualitative approach with descriptive methods to understand the phenomenon under study. The sampling technique used in this study was purposive sampling. The sample in this study was Catholic parents in Saint Pius X Blora Parish who baptized children aged 0-7 years. There were 10 informants, one of the child’s parents (father/mother). Data analysis techniques obtained from interviews, field notes, and documentation are processed through data reduction, data presentation, and conclusions. The results showed that parental involvement in assisting infant baptism preparation that followed could grow their awareness in fulfilling marriage vows. One of the marriage promises to be fulfilled through this research is to educate children’s faith in a Catholic manner.